2017
DOI: 10.25071/2564-4033.40213
|View full text |Cite
|
Sign up to set email alerts
|

Narratives of resistance: (Re) Telling the story of the HIV/AIDS movement – Because the lives and legacies of Black, Indigenous, and People of Colour communities depend on it

Abstract: Centering the narratives of the intersectional struggles within the HIV movement for Indigenous sovereignty, Black and People of Colour liberation, and LGBTQ rights tirelessly fought for by Black, Indigenous, and People of Colour communities legitimates their lives and legacies within the movement; and the relevance of a focused response to the HIV epidemic that continues to wreak devastation in these communities. The recent political push for a post-HIV era solely centers the realities of middle-class white, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This means other forms of knowledge such as Indigenous and Black knowledge are excluded or marginally considered in the planning of climate actions. This leaves municipal actors often somewhat disconnected from the needs and realities of many equity‐ and sovereignty‐seeking groups (i.e., Indigenous groups) resulting in climate action solutions that have unintended consequences (Wilson et al, 2016). Without a deeper understanding of the underlying causes of the lack of engagement, there is a danger for municipal actors to use a “checkbox” approach as a quick superficial fix, that is, equity‐seeking groups are being engaged for the sake of checking a box or fulfilling a requirement rather than more meaningful engagement in decision‐making ( Indigenous Climate Action Summary Report , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This means other forms of knowledge such as Indigenous and Black knowledge are excluded or marginally considered in the planning of climate actions. This leaves municipal actors often somewhat disconnected from the needs and realities of many equity‐ and sovereignty‐seeking groups (i.e., Indigenous groups) resulting in climate action solutions that have unintended consequences (Wilson et al, 2016). Without a deeper understanding of the underlying causes of the lack of engagement, there is a danger for municipal actors to use a “checkbox” approach as a quick superficial fix, that is, equity‐seeking groups are being engaged for the sake of checking a box or fulfilling a requirement rather than more meaningful engagement in decision‐making ( Indigenous Climate Action Summary Report , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Upon refinement, two research team members helped to further refine the themes and ensure the key findings were aligned with the study objectives. In addition, a member checking session was held, in which participants were provided an opportunity to review the initial study findings and provide their feedback on whether the initial results accurately reflected their experiences (Lincoln & Guba, 1985). Of the 10 participants, four attended the member checking session and all confirmed that the initial results were representative of their experiences.…”
Section: Methodsmentioning
confidence: 99%
“…Of the 10 participants, four attended the member checking session and all confirmed that the initial results were representative of their experiences. Finally, the research coordinator documented an audit trail of all methodological and analytic decisions to ensure all decisions were accounted for (Lincoln & Guba, 1985).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation